ELECTRONIC GOVERNMENT AS A TOOL FOR ENSURING THE BALANCE OF INTERESTS OF CITIZENS AND THE STATE - KRAVETS, Iryna; MUKOLETS, Mukola; MATIYCHUK, Nadia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article reveals the essence of electronic governance and its role in ensuring public administration in modern conditions. It was determined that electronic governance is a way of organizing state power with the help of local information network systems and segments of the global information network. This ensures the work of authorities in real time and makes daily communication with them by citizens, legal entities and public organizations as simple and accessible as possible. The organization of e-governance is connected with the development of e-democracy. Electronic governance is a single infrastructure of interdepartmental automated information interaction of state authorities and local self-government with citizens and business entities. The interaction of electronic government with society occurs through the implementation of electronic governance mechanisms at various levels: government with citizens, with business, with officials or employees, automation of relations and document flow between units. It was noted that electronic services are the most important direction in the field of electronic government, because they concern every citizen. The role of e-governance is determined by taking into account the interests of all sides of social relations. The implementation of electronic governance mechanisms is based on public and political activity of citizens, discussion of socially significant issues for society, adoption of common reasonable and well-founded decisions. There are certain risks from the introduction of information technologies in the e-government system, but at the same time they contribute to the development of all spheres of life, strengthen democracy, and increase the activity of the population in social and political life. It was concluded that the development of online services by the state in key areas will ensure prompt access of the population to the necessary services and resources, will make state processes more open and efficient, contributing to the rule of law and the establishment of democratic standards. coexistence of all participants in social relations.